Phenoloxidases of the white-rot fungus Marasmius quercophilus isolated from an evergreen oak litter (Quercus ilex L.) - Tagger, S; Périssol, C; Gil, G; Vogt, G; Le petit, J (Enzyme and Microbial Technology, 1998)
A white-rot basidiomycete, Marasmius quercophilus, was isolated from an evergreen oak litter. This fungus, which very thoroughly bleaches the whole leaf area, produces laccases, a property which has not been studied before. Except on a ground leaf medium, we did not reveal phenoloxidases other than laccases. M. quercophilus is able to transform many aromatic compounds which are by-products of lignin and tannin metabolism. We observed, for example, that lignin monomers, namely p-coumaryl, coniferyl, and sinapyl alcohols are oxidized at different rates by the extracellular crude enzyme extract. The highest production of laccases is obtained with shaking cultures on malt extract supplemented with Tween 80 (0.1%) and CuSO4 (0.5 mg l 21 ). These enzymes have an optimum activity at 80°C and a stable activity at 40°C for 18 h. The extracellular crude enzyme extract medium contains three isoenzymes with pI values of 3.8, 3.5, and 3.2. It is able to significantly reduce the kappa number (21.2%) of a kraft pulp without inclusion of any mediator
Keywords: aromatic compounds; kraft pulp; laccases; Lignin; Marasmius quercophilus; phenoloxidases; tannin monomers

SUCCESSION OF BACTERIA ATTACHED TO EVERGREEN OAK LEAF SURFACES - Périssol, C; Roux, M; LEPETIT, J (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1993)
Heterotrophic attached bacteria were isolated from evergreen oak leaf surfaces (Quercus ilex L.) on both phylloplane and litter at each season during one year. Few epiphytic bacteria were recovered from the phylloplane (18 %) in comparison with the litter. The data derived from the 324 strains were subjected to cluster analysis. The taxonomic structure displayed 44 phenetic groups. The bacterial communities on leaf surfaces belonged mainly to two genera: Bacillus (31 %), present on both phylloplane and litter, and Pseudomonas (35 %) present only on the litter. Some communities of Bacillus were able to degrade structural chemical components of the leaf, such as pectins or lignin monomers. The Bacillus isolates were generally more numerous in spring and in summer, i.e. during the warm seasons, whereas Pseudomonas predominated in autumn and winter. In vitro measurements of strains growth rates showed moreover that Bacillus strains grew better at 40-degrees-C than Pseudomonas strains. A climate-related factor, namely temperature, has therefore a great influence on the natural selection process of these communities. Another seasonal succession was observed, involving two genera: Xanthomonas predominant in winter and Lactobacillus in summer, as well as the Enterobacteriaceae family in autumn.
Keywords: ATTACHED BACTERIA; leaves; litter; PHYLLOPLANE